1974
DOI: 10.1097/00000658-197408000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy of Malignant Melanoma with Dimethyl Triazeno lmidazole Carboxamide (DITC) and Nitrosourea Derivatives (BCN U, CCNU)

Abstract: Chemotherapy for metastatic melanoma was performed in 80 consecutive evaluable patients. DTIC, BCNU and CCNU produced responses in 28% of patients, alone or in combination with each other. Three of 62 patients treated with DTIC remain free of tumor, off therapy at 18-36 months following objective regression of metastases. Chemotherapy with commercially available drugs continued to be uniformly unsuccessful. DTIC was used successfully in treatment of extensive extracranial disease, including one patient with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…In our study, chemotherapy was delayed in cases where the maternal status was fragile and required rapid caesarean section to rescue the baby. Taking into account our patients, 36 administrations of dacarbazine during pregnancy have been documented, eight during the first trimester, 8,11,26–28 and 28 during the second or third trimester 9,10,27–32 . Congenital abnormalities were observed during the first trimester exposure in two cases and consisted of isolated microphthalmos with secondary severe hypermetropia, 11 and in a unilateral floating thumb malformation 28 .…”
Section: Discussionmentioning
confidence: 98%
“…In our study, chemotherapy was delayed in cases where the maternal status was fragile and required rapid caesarean section to rescue the baby. Taking into account our patients, 36 administrations of dacarbazine during pregnancy have been documented, eight during the first trimester, 8,11,26–28 and 28 during the second or third trimester 9,10,27–32 . Congenital abnormalities were observed during the first trimester exposure in two cases and consisted of isolated microphthalmos with secondary severe hypermetropia, 11 and in a unilateral floating thumb malformation 28 .…”
Section: Discussionmentioning
confidence: 98%
“…The studies of Johnson and Jacobs (1971) and Nathanson et al (1971) have shown that DTIC has a greater effect in females than in males. On the negative side, Hill et al (1974) studied 107 patients after surgery for malignant melanoma by random assignment to receive or not to receive DTIC. No significant difference was found in the average survival times between the treated and the untreated groups.…”
Section: Section 18amentioning
confidence: 99%
“…Dacarbazine alone produced objective responses in 29% of patients in a series of 80 consecutive cases of metastatic melanoma,48 and it rapidly became the standard against which other agents were judged. By 1975, >800 patients had been treated, with an overall response rate of 25% 49.…”
Section: Discussionmentioning
confidence: 99%